Effect of Traditional Chinese Medicine bamboo cupping therapy combined with hot compress in the treatment of lumbar disc herniation (中药竹罐联合中药热敷治疗腰痹症效果观察) - ZHANG Zhe (张喆); KANG Jingjing (康京京); SUN Feifei (孙飞飞); WANG Aiying (王艾莹); JIA Minting (贾旻婷) (Association of Integrative Nursing, 2023)
Objective To investigate the effect of Traditional Chinese Medicine (TCM) bamboo cupping therapy combined with hot compress in the treatment of lumbar disc herniation (LDH). Methods Totally 50 LDH patients were recruited as research subjects . TCM bamboo cupping therapy combined with hot compress was carried out 2 times per day, 5 days per treatment course. The efficacy of treatment was measured after a two-course treatment. Results The total effective rate was 96. 00%(48/50). Conclusion The TCM bamboo cupping therapy combined with hot compress is effective in the treatment of LDH. (目的 观察中药竹罐联合中药热敷治疗腰痹症的临床疗效。方法 选取腰痹症患者50例为研究对象, 采用中药竹罐联合中药热敷疗法治疗, 2次/d, 5 d为1个疗程, 治疗2个疗程之后评估疗效。结果 痊愈32例, 显效10例, 有效6例, 无效2例, 有效治愈率为96. 00%(48/50)。结论 中药竹罐联合中药热敷治疗腰痹症疗效明确。)